Global patterns and drivers of phylogenetic structure in island floras - Patrick Weigelt; W. Daniel Kissling; Yael Kisel; Susanne A. Fritz; Dirk Nikolaus Karger; Michael Kessler; Samuli Lehtonen; Jens‐Christian Svenning; Holger Kreft (United Kingdom, 2022)
Islands are ideal for investigating processes that shape species assemblages because they are isolated  and have discrete boundaries. Quantifying phylogenetic assemblage structure allows inferences in-situ speciation. Here, we link phylogenetic assemblage structure to island characteristics across 393 islands worldwide  and 37,041 vascular plant species (representing angiosperms overall, palms and ferns). Physical and  bioclimatic factors, especially those impeding colonization and promoting speciation, explained  more  variation  in  phylogenetic  structure  of  angiosperms  overall  (49%)  and  palms  (52%)  than  of  ferns consistent with their dispersal- and speciation-related traits and climatic adaptations. Phylogenetic  diversity was negatively related to isolation for palms, but unexpectedly it was positively related large-seeded, animal-dispersed palm family whereas colonization from biogeographically distinct in-situ among taxonomic groups on islands, which sheds light on the origin of insular plant diversity.